Pengaruh Perputaran Modal Kerja, Likuiditas Dan Pertumbuhan Aktiva Terhadap Profitabilitas Perusahaan - Widyani Sekar Ramadhania; Anggit Dyah Kusumastuti; Prima Prihatini (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to determine the effect of working capital turnover, liquidity, and asset growth on profitability in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. This research was conducted based on information on the Indonesia Stock Exchange (IDX). This research used a non-participant observation method and the determination of sampling used a purposive sampling method. There are 12 Food and Beverage Sub-Sector Manufacturing companies as samples in this study. The results show that working capital turnover (WCTO), liquidity (Quick Ratio) partially has no effect and is not significant on profitability (ROE) and asset growth partially significant effect on profitability (ROE). The ability of the independent variable to explain the dependent variable is very low, it is indicated by the coefficient of determination R square of 15.1%.